The possibility of reducing the risk of suicidal attempt in adolescents by practicing Confucian philosophy: a phenomenological study in Vietnam - Giang, Thien-Vu; Nguyen-Ngoc, Phi-Bao; Sam, Vinh-Loc; Huynh, Van-Son (Frontiers in Psychology, 2025)
IntroductionSuicide attempt in adolescents is a concern topic that differs greatly between countries because of its cultural specificity. This article reported on the possibility of reducing the risk of suicide attempts in adolescents by practicing Confucian philosophy.MethodsIn this study, Confucian philosophy is approached as an educational philosophy applied in clinical practice on 12 adolescents who used to attempt suicide. Using a phenomenological study design, we interviewed the selected participants to describe themes surrounding the impact of practicing Confucian philosophy on cognition, emotions, and behaviors related to suicide attempts.ResultsFrom this framework, we explored the three main findings, which described the journey of reconnecting and repairing family relationships fractured by the negative influence of remnants of Vietnamese Confucianism families. The conservatism and remnants of traditional Confucianism have influenced how Vietnamese parents raise their children, leading to increased risks of suicide as adolescents.DiscussionThe discovered themes greatly contribute to the process of clinical intervention for adolescents who have attempted suicide in countries with similar cultures to Vietnam, or accepted Confucianism as a neutral approach. Above all, the self-nurture and neutral lifestyle were resources that helped the adolescents cope better with their personal problems after participating in this study.